In silico pharmacological study of AQP2 inhibition by steroids contextualized to Ménière’s disease treatments - Mom, Robin; Réty, Stéphane; Mocquet, Vincent; Auguin, Daniel (Frontiers in Neurology, 2023)
Ménière’s disease (MD) is characterized by an abnormal dilatation of the endolymphatic compartment called endolymphatic hydrops and is associated with fluctuating hearing losses and vertigo. Corticosteroid treatment is typically administered for its anti-inflammatory effects to MD patients. However, we recently described for the first time a direct interaction of two corticosteroids (dexamethasone and cortisol) with human AQP2 which strongly inhibited water fluxes. From these initial studies, we proposed an AQPs Corticosteroids Binding Site (ACBS). In the present work, we tested the interaction of 10 molecules associated to the steroid family for this putative ACBS. We observed a wide diversity of affinity and inhibitory potential of these molecules toward AQP2 and discussed the implications for inner ear physiology. Among the tested compounds, cholecalciferol, calcitriol and oestradiol were the most efficient AQP2 water permeability inhibitors.